2021
DOI: 10.1108/rpj-02-2021-0034
|View full text |Cite
|
Sign up to set email alerts
|

An in-process multi-feature data fusion nondestructive testing approach for wire arc additive manufacturing

Abstract: Purpose The major problem that limits the widespread use of WAAM technology is the forming quality. However, most of the current research focuses on post-process detections that are time-consuming, expensive and destructive. This paper aims to achieve the on-line detection and classification of the common defects, including hump, deposition collapse, deviation, internal pore and surface slag inclusion. Design/methodology/approach This paper proposes an in-process multi-feature data fusion nondestructive test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The process conditions and distortion relation appeared to be highly nonlinear. The box-cox transformation revealed that the −1/2 power of distortion (d) could be linearly expressed as a function of parameters under study, as shown in Equations ( 1) and (2). The significant main factors and interactions were identified with stepwise regression.…”
Section: Distortion With Passive and Active Thermal Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The process conditions and distortion relation appeared to be highly nonlinear. The box-cox transformation revealed that the −1/2 power of distortion (d) could be linearly expressed as a function of parameters under study, as shown in Equations ( 1) and (2). The significant main factors and interactions were identified with stepwise regression.…”
Section: Distortion With Passive and Active Thermal Managementmentioning
confidence: 99%
“…One such additive manufacturing method is the use of a gas metal arc welding (GMAW) process, known as Wire-Direct Energy Deposition (W-DED) or Wire Arc Additive Manufacturing (WAAM). Low capital and operating costs, high deposition rates and material efficiency are some of the benefits of WAAM, making it ideal for manufacturing large structural components widely used in marine, aerospace, defence and transportation [2,3]. WAAM has successfully fabricated super alloys, which are functionally graded materials that have tailored properties for various industrial applications [4].…”
Section: Introductionmentioning
confidence: 99%
“…Optical sensors are used to determine the geometric parameters of deposited layers and to establish a database for the corresponding process parameters. Based on such a database, a regression network of current vs the deposited layer geometry can be established (Wang et al , 2022; Zeng et al , 2021; Chen et al , 2021). An active disturbance rejection control is applied to adjust the current in real time and improve the precision (Wang et al , 2021; Wang et al , 2021).…”
Section: Feedback Control Of Sensor Systemsmentioning
confidence: 99%
“…It has been shown that the repaired components are prone to generate surface cracks, which can seriously affect the repair quality and even leads to the mechanical failure of the repaired components. Therefore, the nondestructive testing of surface cracks is required to guarantee the quality and structural integrity of repaired components, a challenge which receives much attention from industry and academia [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%